LncRNA-AL035458.2/hsa-miR-181a-5p Axis-Mediated High Expression of NCAPG2 Correlates With Tumor Immune Infiltration and Non-Small Cell Lung Cancer Progression - Chen, Xi; Guo, Jishu; Ren, Wenjun; Zhou, Fan; Niu, Xiaoqun; Jiang, Xiulin (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) is the most common histological lung cancer, and it is the leading cause of cancer-related deaths worldwide. NCAPG2 (non-SMC condensin II complex subunit G2) has been shown that upregulation in various human cancers. Nevertheless, the underlying biological function and potential mechanisms of NCAPG2 driving the progression of lung adenocarcinoma remains unclear. In this study, we investigated the role of NCAPG2 in lung adenocarcinoma and found that the expression of NCAPG2 in LUAD tissues was significantly higher than that of NCAPG2 expression in adjacent normal tissues. Kaplan-Meier survival analysis showed that patients with higher NCAPG2 expression correlated with unfavorable clinical outcomes. ROC curve analysis showed that the AUC value of NCAPG2 was 0.914. Correlation analysis showed that NCAPG2 expression was associated with immune infiltration in LUAD. Finally, we found that AL139385.1 was upregulated in LUAD cancer tissues and cell lines. Knockdown of NCAPG2 inhibited cell proliferation, cell migration, and cell invasion of lung adenocarcinoma in vitro. More importantly, we established AL035458.2/hsa-miR-181a-5p axis as the most potential upstream ncRNA-related pathway of NCAPG2 in LUAD. In conclusion, our data demonstrated that ncRNAs-mediated high expression of NCAPG2 was correlated with progression and immune infiltration, and could serve as a prognostic biomarker for lung adenocarcinoma.